Chromosomal Abnormalities Associated with Neural Tube Defects (II): Partial Aneuploidy - Chih-Ping Chen (Elsevier, 2007)
Fetuses with neural tube defects (NTDs) carry a risk of chromosomal abnormalities. The risk varies with maternal age, gestational age at diagnosis, association with other structural abnormalities, and family history of chromosome aberrations. This article provides a comprehensive review of structural chromosomal abnormalities associated with NTDs, such as del(13q), r(13), dup(2p), del(2q), del(1p), del(1q), dup(1q), del(3p), dup(3p), del(3q), dup(3q), del(4p), dup(4p), del(4q), dup(4q), del(5p), del(6p), dup(6q), del(6q), dup(7p), del(7q), dup(8q), del(9p), del(10q), del(11q), dup(11q), dup(12p), dup(14q), del(14q), del(15q), dup(16q), del(18q), r(18), dup(20p), +i(20p), del(22q), del(Xp), and dup(Xq). NTDs may be associated with aneuploidy. Perinatal identification of NTDs should alert one to the possibility of chromosomal abnormalities and prompt a thorough cytogenetic investigation and genetic counseling.